A RETROSPECTIVE ANALYSIS ASSESSING THE FREQUENCY OF PATIENTS WILLING TO UNDERGO RETREATMENT OF ORTHODONTIC TREATMENT AFTER RELAPSE - Antony, Monica; Mary Varghese, Remmiya; L. , Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Orthodontic relapse is the tendency for teeth to return to their pre-treatment position. It is difficult for the tooth to be maintained in the corrected position that was achieved by orthodontic treatment without proper retention. Factors that cause the teeth to move back to original malocclusion include periodontal, gingival, occlusal, and growth-related factors. The aim of the study is to assess the frequency of patients willing to undergo retreatment of orthodontic treatment after relapse. Materials and methods: 588 data points were collected on the study population between June 2010 and April 2020 that had removable orthodontic treatment done due to relapse. The data was imported to the software IBM SPSS Version 23.0 and analyzed using descriptive statistics and Pearson’s correlation. Graphs were obtained, and the results were tabulated. Statistical significance was set at <0.05. Results: Out of the total study population who have been treated with removable appliances, 33.50% of the study population had undergone retreatment, and 28.57% of the population that had undergone treatment were new cases that were in the age group of 21 to 30 years. 54.08% of the study population that underwent orthodontic treatment were females, of which 27.04% were retreatment and 27.04% were new cases, and 45.92% were males, of which 23.64% were retreatment and 22.28% were new cases. Conclusion: Relapse being unpredictable, it is important to educate the patients to be fully committed when undergoing orthodontic treatment. The patient should be dedicated to wearing the retainer and also made to understand that by wearing the retainer as directed, it will help the teeth along with the surrounding hard and soft tissues to realign, stabilizing the new bite.